2008
DOI: 10.1007/s11149-008-9069-9
|View full text |Cite
|
Sign up to set email alerts
|

Implications of CO2 emissions trading for short-run electricity market outcomes in northwest Europe

Abstract: We examine the short-run implications of CO 2 trading for power production, prices, emissions, and generator profits in northwest Europe in 2005. Simulation results from a transmission-constrained oligopoly model are compared with theoretical analyses to quantify price increases and windfall profits earned by generators. The analyses indicate that the rates at which CO 2 costs are passed through to wholesale prices are affected by market competitiveness, merit order changes, and elasticities of demand and supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(58 citation statements)
references
References 27 publications
7
51
0
Order By: Relevance
“…Empirical studies [7,9] estimating the pass through rates of CO2 costs to power prices in EU countries [7] found that pass through rates range between 60% and 120% in EU countries under the assumption of perfect competition, while [9] showed that this rate is over 100% for The Netherlands, Belgium, Germany and France. In addition, [20] also found that cost pass through rates are close to 100% when the demand is inelastic, while this rate fell to around 80% with elastic demand.…”
Section: Distinctive Features Of the Korean Etsmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical studies [7,9] estimating the pass through rates of CO2 costs to power prices in EU countries [7] found that pass through rates range between 60% and 120% in EU countries under the assumption of perfect competition, while [9] showed that this rate is over 100% for The Netherlands, Belgium, Germany and France. In addition, [20] also found that cost pass through rates are close to 100% when the demand is inelastic, while this rate fell to around 80% with elastic demand.…”
Section: Distinctive Features Of the Korean Etsmentioning
confidence: 99%
“…Lower demand elasticity for electricity would increase the level of cost pass through [9,20,21], making the inclusion of the indirect emissions within the ETS have very little effect. Thus, the value for demand elasticity of electricity has been calculated by running the BAU scenario with an exogenous output tax increase/decrease by 1% on the electricity sector.…”
Section: Modelling Direct and Indirect Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors find that the aggregated power generation sector benefits even if allowances are fully auctioned. This is shown for the UK (Martinez and Neuhoff 2005) and for Northwestern Europe (Chen et al 2008). Similarly, Burtraw et al (2002) report for the US that only 9% of all allowances would need to be grandfathered to preserve total producer profits when introducing CO2 certificates.…”
Section: Literature Reviewmentioning
confidence: 94%
“…5 In comparison, our equilibrium pass-through rate (with unconditional allocation of quotas) is actually 3 For instance, Bunn and Fezzi (2007) for the UK, and Kirat and Ahamada (2011) for Germany and France. 4 See Chen et al (2008) for an earlier version of the same model. 5 For instance, Sijm et al (2006) for Germany and the Netherlands, Simshauser andDoan (2009) for Australia, andFell (2010) for the Nordic market.…”
Section: Introductionmentioning
confidence: 99%